Evaluation of Asynchronous Learning Implementation Using the CIPP Model in the Social Studies Education Program at Al-Fatimah Islamic Institute Bojonegoro - Armawati Hidayati; Bachtiar S. Bachri; Irena Yolanita Maureen (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This research aims to evaluate the implementation of asynchronous learning conducted by the Tadris IPS study program at IAI Al-Fatimah Bojonegoro. Asynchronous learning refers to virtual (online) face-to-face learning facilitated through the internet. It is also commonly referred to as online learning. The evaluation of asynchronous learning was carried out using the CIPP (Context, Input, Process, Product) model. This evaluation research employed a simple experimental method by distributing questionnaires to lecturers and students of Tadris IPS, who have been using asynchronous learning for the past two semesters. The research data were collected through a questionnaire completed by 30% of the 37 students enrolled in the Tadris IPS study program. The evaluation focused on the level of agreement or disagreement among students, as beneficiaries of asynchronous learning, regarding the content, the presentation of materials, the adequacy of resources in supporting the quality of asynchronous learning, and the achievement of learning objectives. The results indicate that asynchronous learning is sufficiently effective and can be continued for future academic sessions. It was also proven that students are able to comprehend the materials presented, meaning that learning objectives were achieved. However, several shortcomings were identified, including the limited use of visual content such as images, videos, and audio, which could enhance learning references. Furthermore, there is a need for policies to support the provision of paid applications to improve the resources available for asynchronous learning